Concept Design of a Tram Bogie with Atypical Suspension - Hauser, Vladimir; Kravchenko, Kateryna; Loulova, Maria; Nozhenko, Olena; Harusinec, Jozef; Pavlik, Alfred; Fomin, Oleksij (Manufacturing Technology Journal, 2019)
In the urban railways environment, there is considerable stress of the track due to operation, which results in extensive deformation of the track geometric position, wear of the rail heads, expansion of the free channel of the track, leading to an increase in steering forces in the rail-wheel contact and further worsening of the situation. The authors perceive this situation primarily as a consequence of an inappropriate bogie concept of the operating vehicles - not of the track quality. The article focuses on designing a new bogie concept that takes into account the specific environmental conditions for which it is intended. The presented bogie design is characterized by the mounting of the frame on the wheelsets by means of three bearing boxes and the presence of a mechanism for adjusting the radial position of the wheelsets during ride in track arcs. This is a new, unconventional solution for which a number of patent applications have been filed. Simulation analyzes of vehicle ride with the designed bogie are currently underway. On the basis of the first results, it is foreseen that the design will increase the life of the track several times, reduce the energy consumption of vehicles and the environmental load of the environment through the transport system.
Keywords: track-friendly bogie; wheel load deviation; tram bogie concept; wheelset positioning in track curve